Regulation of the apothecary activity in Bosnia and Herzegovina over the Austro-Hungarian period - Vanda Marković-Peković (Medicinski glasnik, 2021)
Aim: To present the regulations governing the operation of pharmacies in Bosnia and Herzegovina over the Austro-Hungarian rule (1878-1918). Methods: Qualitative secondary data analysis was used. Results: The Austro-Hungarian government had found poor population’s health, insufficient health facilities and qualified staff. For a long time, population was treated by old methods of medicine and pharmacy, and directed to folk doctors, healers and herbalists. As early as 1879, orders requesting mandatory possession of a university diploma to practice pharmacy and medicine, thus taking the initial steps to combat quackery. The production and dispensing of medicines became the exclusive competence of pharmacists. The Law on Pharmacies adopted in 1907 comprehensively regulated the apothecary activity. Pharmacy Gremium was founded, the first association of pharmacists with the task of protecting professional interests. All types of quackery were explicitly forbidden to pharmacy staff. Apothecary activity was regulated as a craft, not as a health activity. During this period, pharmacy became a regulated profession with educated and qualified personnel. The number of public pharmacies and qualified staff was growing. In 1878 only one graduated pharmacist was found, while in 1910 in 47 pharmacies there were 79 pharmacy staff. At the end of 1918, the masters of pharmacy were the owners of 48 pharmacies, in 38 cities. Conclusion: All enacted regulations contributed to the development and improvement of the apothecary activity over the observed period, and laid the foundations for the future development of the profession.
Keywords: community pharmacies; history of pharmacy; legislation